Optimization of enzymatic assay of superoxid dismutase and glutation peroxidase activity in milk whey - Trajchev, M., Nakov, D., Gjorgoski, I. (Faculty of Agricultural Science and Food, 2015)
General spectrofotometric kinetic protocols are described to measure the antioxidant enzyme activity of superoxide dismutase (SOD) and glutathione peroxidase (GPx) in milk whey. The SOD convert superoxide radical into hydrogen peroxide and molecular oxygen, while the GPx convert hydrogen peroxide into water. In this way, two toxic species, superoxide radical and hydrogen peroxide, are converted to the harmless product water. The applicability of this methods for milk samples from dairy cows were tested. SOD activities in the milk whey was determined by the autoxidation of pyrogallol in presence of DTPA in TRIS-HCl buffer, pH= 8.5. The effect of reaction conditions on enzymatic inhibition of pyrogallol autooxidation was studied when different amounts of sample were added in reaction mixture. The reaction mixture for determination of GPx activity contained EDTA, reduced glutathione, glutathione reductase, NADPH and cumene hydroperoxide in phosphate buffer, pH= 7.6. The effect of reaction conditions on enzymatic NADPH consumption was studied when different amounts of reduced glutathione and whey sample were added in reaction mixture. The both spectrophotometric methods were modified in order to accommodate kinetic analyses in 96-well micro plates. The rate of pyrogallol autooxidation and NADPH oxidation linearly depend from amount of whey sample in reactive mixture. Applying higher amounts of milk whey in reactive mixture was decreasing optical density reading of pyrogallol autooxidation at 415 nm and increasing the optical density readings of NADPH oxidation at 340 nm, in a linear way. The methods could be validly applied for milk whey samples.
Keywords: dairy cows, milk whey, superoxid dismutase, glutathion peroxidase